Effect of exercise-meal timing on energy intake, appetite and food reward in adolescents with obesity: The TIMEX study. (1st March 2020) - Fillon, A.; Mathieu, M.E.; Masurier, J.; Roche, J.; Miguet, M.; Khammassi, M.; Finlayson, G.; Beaulieu, K.; Pereira, B.; Duclos, M.; Boirie, Y.; Thivel, D.
Abstract: The present study manipulated the delay between exercise and test meal to investigate its effect on energy intake, appetite sensations and food reward in adolescents with obesity. Fifteen adolescents with obesity randomly completed 3 experimental sessions: i) rest without exercise (CON); ii) 30 min of exercise 180 min before lunch (EX-180); iii) 30 min of exercise 60 min before lunch (EX-60). Ad libitum energy intake was assessed at lunch and dinner, and food reward (LFPQ) assessed before and after lunch. Appetite sensations were assessed at regular intervals. Absolute energy intake was not different between conditions despite a 14.4% lower intake in EX-60 relative to CON. Lunch relative energy intake (REI: energy intake – exercise-induced energy expenditure) was higher in CON compared with EX-60 (p < 0.001). Lunch fat intake was lower in EX-60 compared with CON (p = 0.01) and EX-180(p = 0.02). Pre-lunch hunger in CON was lower than EX-180 (p = 0.02). Pre-lunch prospective food consumption and desire to eat were lower in CON compared with both exercise conditions (p = 0.001). A significant condition effect was found for explicit liking for high-fat relative to low-fat foods before lunch (p = 0.03) with EX-60 being significantly lower than EX-180 (p = 0.001). The nutritional and food reward adaptations to exercise might be dependent on the timing of exercise, which is of importance to optimize its effect on energy balance in adolescents with obesity. Clinical trial reference: NCT03807609.